Insights into technical challenges in the field of microplastic pollution through the lens of early career researchers (ECRs) and a proposed pathway forward - Danopoulos, Evangelos; Stanton, Thomas; Ma, Yini; Horton, Alice A.; Chen, Qiqing; Levermore, Joseph M.; Li, Jiana; McGoran, Alexandra R.; Lai, Yujian; Nolte, Stefanie; Li, Ruilong; Alvarez Barrantes, Lucrecia; et al. (Frontiers in Earth Science, 2023)
Early career researchers (ECR) face a series of challenges related to the inherent difficulties of starting their careers. Microplastic (MP) research is a topical field attracting high numbers of ECRs with diverse backgrounds and expertise from a wealth of disciplines including environmental science, biology, chemistry and ecotoxicology. In this perspective the challenges that could hinder scientific, professional, or personal development are explored, as identified by an international network of ECRs, all employed in MP research, that was formed following a bilateral workshop for scientists based in the UK and China. Discussions amongst the network were grouped into four overarching themes of technical challenges: in the field, in the laboratory, in the post data collection phase, and miscellaneous. The three key areas of representativeness, access to appropriate resources, training, and clean labs, and the use of databases and comparability, as well as the overarching constraint of available time were identified as the source of the majority of challenges. A set of recommendations for pathways forward are proposed based on the principles of research openness, access to information and training, and widening collaborations. ECRs have great capacity to promote research excellence in the field of MPs and elsewhere, when provided with appropriate opportunities and suitable support.